Peranan Silaturahim Dalam Komunikasi Bisnis Pada Kesuksesan Pengusaha Batik Jetis Sidoarjo - Althaf Aulia Chisty; Siti Inayatul Faiza (Jurnal Ekonomi Syariah Teori dan Terapan, 2014)
This study aims to identify and explain how gathering in business communication that occurs in batik entrepreneurs at Jetis, Sidoarjo are able to play a role in achieving entrepreneurial success. This theme will be the basic reason for explaining the role of gathering in business communication on batik entrepreneurs' success that has been achieved at Jetis, Sidoarjo. The gathering is conducted between businessmen in local scope and outside of Sidoarjo, and the craftsmen and other employees.This study used a qualitative approach with descriptive methods. Data was collected through documentation, interviews, and direct observation to study the object. To test the validity of data, this study uses three triangulations such as triangulation of sources, theories, and methods.The research result showed that gathering in business communication conducted by batik entrepreneurs at Jetis, Sidoarjo, intended for the survival and success in batik entrepreneurship, as well as in the context of observance. Implementation gathering conducted in jetis, Sidoarjo's batik entrepreneurship is the formation of batik association in Sidoarjo, beside that gathering also help the entrepreneurs to made business collaborations between other batik entrepreneurs and create working atmosphere of kinship. It helps the entrepreneur to developing their business and achieve success. REFERENCES Afzalurrahman. 2000. Muhammad Sebagai Seorang Pedagang. Terjemahan dari Muhammad encyclopedia of seerah. Jakarta: Yayasan Swarna Bhumy.Ahlam, Abdullah. 2013. “Kunci Sukses Bisnis Keturunan arab Di Kawasan Ampel surabaya”. Skripsi tidak diterbitkan. Program Sarjana Universitas Airlangga.Ali, Kamal. 2007. Berbisnis Dengan Cara Rasul. Bandung: Jembar.Alma, Buchari dan Donni Juni Priansa. 2009. Manajemen Bisnis Syariah. Bandung:Alfabeta.Al-Munawwir.1999. Kamus Arab-Indonesia Terlengkap. Edisi Kedua. Jakarta.Al-Qu’ayyid, Ibrahim bin Hamd. 2005. 10 Kebiasaan Muslim yang Sukses. Jakarta: Maghfirah Pustaka.Al-Quran dan Terjemahannya.2005. Departemen Agama Republik. Indonesia,Jakarta.Al-raghib al-asfahani.2004. Mu’jam almufradat li Al-faz Al-quran, (online), (https://archive.org/details/Mufrad atalQuran-Raghib , diakses 10 Oktober 2013).Anna, Mariana dan Milah Nurmilah. 2012. Berkah dan Manfaat Silaturahmi. Jakarta: Ruang kata.Antonio, Muhammad Syafi’i. 2007. Muhammad SAW The Super Leader Super Manager. Jakarta: Prenada Media. Faisal. Lalu Muchsin Efendi.Arwani, Ahmad. 2010. Kunci Sukses Berbisnis: Ala Rasullulah SAW. Jakarta: Inti Media.Bahreizy, Hussein. 2001. Hadis Shohih Bukhari: Himpunan Hadis Pilihan. Surabaya: Al-Ikhlas.Basrowi, 2011. Kewirausahaan Untuk Pegawai Tinggi Negeri. Cetakan pertama. Bogor: Ghalua Indonesia.Chapra, M.Umer. 2000. “Islam Dan Tantangan Ekonomi”. Cetakan Pertama, Jakarta, Gema Insani.Dahlan, Abdullah. Asis. et. Al. 1996. Ensiklopedi Hukum Islam. IV. Jakarta: Ichtiar Baru Van Hoeve.Departeman Pendidikan Nasional.2005. Kamus Besar Bahasa Indonesia. Edisi Keempat, Jakarta.Gramedia Pustaka Utama.Dewi, Sutisna. 2006. “Komunikasi Bisnis”. Yogyakarta. CV ANDI OFFSET.Drucker, Peter F. (1996). Inovasi dan kewiraswastaan. Erlangga, Jakarta.Dumairy. 1997. Perekonomian Indonesia. Jakarta: Rineka Cipta.Elfindri, dkk. 2010. “Minang Entrepreneurship, Filosofi Dan Rahasia Sukses Etis Minang Membangun Karakter Kewirausahaan”. Jakarta, Badouse Media.Faizah, Siti Inayah. 2012. Kewirausahaan Dalam Perspektif Agama dan Budaya (Study fenomenologi Konstruktif Wirausahawan Etnis Tionghoa Muslim).Surabaya. Universitas Airlangga (2009).Himstreet, William C; Baty, Wayne Murlin. Bussines Communications : Priciples and Methods. Boston : PWS-kent Publishing Company, 1990.Jauhar, Ahmad Al-Mursi Husain. 2010. “Maqashid Syariah”. Jakarta: Amzah M.Wiratmo. 1996. Pengantar Kewiraswastaan, Kerangka Dasar Memasuki Dunia Bisnis.Yogyakarta. BPFE.Moleoong. 1988. Metodelogi Penelitian Kualitatif. Bandung: PT. Rosdakarya.Muhammad, bin Abdullah.2010. Tafsir Ibnu Katsir.Surakarta: Pustaka Imam Syafi’i.